Effect of process conditions on properties of biochar from agricultural residues - Waranya Somparn (2020)
© 2020 Institute of Physics Publishing. All rights reserved. In northern Thailand, there are a great amount of agricultural residues generated after the harvest, most of which are burned as a means of disposal, affecting the soil for agriculture, wild animals, as well as causing air pollution. One of the solutions that may be beneficial in terms of carbon credit is to turn these agricultural residues into biochar using slow pyrolysis. Biochar is widely accepted biologically derived matter with the ability to contain carbon, large amount of nutrients, adding biodiversity in soils. The attribute of biochar is varied depending on its production process. This research aims to study biochar production conditions and possible attributes with slow pyrolysis process under 100 ml/min nitrogen condition. Two types of agricultural residues including rice husk and corn cob were used, at the process temperature of 300-700 °C. The results indicated that when the temperature was increased, the produced biochar decreased, but different amounts of carbon, electrical conductivity, amounts of inorganic minerals (N, P, K, Mg, Ca, Fe), and alkalinity increased. This enabled the produced biochar to add more carbon to the soil when used, reduce acidity or alkalinity, as well as help the soil to contain more water and other required nutrients for plants better and become a home to microbe. More air ventilation was allowed in the soil, improving its quality.